Cenas e discursos heteronormativos e de gênero na educação infantil - Almeida, Cássia Cristiane Lopes de (2020)
In Early Childhood Education, binary gender and heteronormative discourses are frequent. I present in this research scenes and discourses of gender and heteronormativity that are articulated with theoretical references about gender and heteronormativity in education. The methodological perspective is qualitative and started from the memories of a teacher-researcher and also from semi-structured interviews carried out with education professionals, with the objective of understanding if and when gender and heteronormativity are present in the work of teachers, education assistants, managers and employees in Early Childhood Education. It has been observed that these people are reproducing in their pedagogical practices and/or in their speeches the binarisms of gender and heteronormative control of children's bodies, determining what is allowed and forbidden to boys and girls on the basis of biological sex, Christian religious conceptions and what has been learned historically and culturally. Some advances were seen in the course of the research, but the colour pink and blue is still a determining factor in children's toys, belongings and activities, and also expresses gender binarism. It was found that the teachers who embraced the change in their pedagogical practices were in search of continuous training and, from this, began the process of personal deconstruction and, consequently, the change in pedagogical practices that, until then, were binary and heteronormative. It concludes with the need to promote the continued training of teachers in gender and sexuality and new research that explores these issues from an intersectional point of view in early childhood education.